Muchelney Abbey
Very few sacred building were constructed during this period- a contrast to the great numbers of churches and adjoining buildings built during the preceding centuries. In fact, the power of the monasteries was so reduced that independence from religious domination became one of the principal aims of the Tudors. In 1539, the Church in England was reformed and the great abbeys and monasteries were taken over by the State and their great wealth confiscated. In most cases, the abbey churches were sold to the parishioners, as here at Muchelney where the abbot's house, seen on the left, became the farmhouse for the former abbey lands.